Whole genome sequence and manual annotation of Clostridium autoethanogenum, an industrially relevant bacterium - Humphreys, Christopher M.; McLean, Samantha; Schatschneider, Sarah; Millat, Thomas; Henstra, Anne M.; Annan, Florence J.; Breitkopf, Florence; Pander, Bart; Piatek, Pawel; Rowe, Peter; Wichlacz, Alexander T.; Woods, Craig; et al. (BioMed Central, 2015)
Clostridium autoethanogenum is an acetogenic bacterium capable of producing high value commodity chemicals and biofuels from the C1 gases present in synthesis gas. This common industrial waste gas can act as the sole energy and carbon source for the bacterium that converts the low value gaseous components into cellular building blocks and industrially relevant products via the action of the reductive acetyl-CoA (Wood-Ljungdahl) pathway. Current research efforts are focused on the enhancement and extension of product formation in this organism via synthetic biology approaches. However, crucial to metabolic modelling and directed pathway engineering is a reliable and comprehensively annotated genome sequence.